Monitoring of Total Hydrocarbons and Particulate Matters in AL Nasiriya City, South of Iraq. - Mohsin A. Mashkhool ,; Nayyef M. Azeez ,; Salwa A. Abduljaleel, (University of Thi-Qar Journal of Science, 2021)
In the current study concentrations of some air pollutants included total hydrocarbons (THCs) and particulate matter (PM10) were estimated. Samples were collected monthly from January to December 2020 in five stations in AL- Nasiriya City. Stations 1, 2, 3, and 4 were located at industrial, commercial, and residential areas, respectively, while the fifth station was located in a rural area. The Horiba Mobile Laboratory monitored air pollutants was used in the study for the estimation, it contains a mobile ambient air quality monitoring system. The results showed a variable concentrations of THCs and PM10 among seasons and stations during the study period. The highest value was found in Station 3 for THCs, while the highest concentration for PM10 was in stations 2, 3, and 4, respectively. Moreover, the results showed variable AQI values in all stations of the study for PM10. In general, all concentrations of PM10 were above the WHO and Iraqi standards.